Physicochemical and Spectrometric Evaluation of Co-Processed Maize Starch B.P. and Alpha-Lactose Monohydrate - Oduola, A. R; Okpanachi, G. O.; Ohwoavworhua, F.O.; Danladi, M. F.; Iji, M. E.; Bwala, J. A.; Maikifi, S. A.; Bwala, A. S. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Co-processing is based on the concept of two or more excipients interacting at molecular level, the objective of which is to provide a synergy of improved functionality as well as masking the undesirable properties of individual materials. The aim of this research was to evaluate the physicochemical and spectrometric properties of co - processed Maize Starch B.P. and α - lactose monohydrate. Various proportions of Maize Starch B.P. and α - lactose monohydrate (90:10, 92.5:7.5, 95:5, 97.5:2.5), based on principles of co-processing were prepared using the solvent evaporation method (co – drying), and characterized using Angle of repose, Carr’s index, Hausner’s ratio and swelling capacity. The proportion of excipients (92.5:7.5) with the best flowability and compressibility was selected and further investigated for compatibility studies to check for excipient – excipient interaction, using Fourier Transform Infrared (FTIR). All the co-processed excipients showed good flow properties (as reflected in the Angle of repose of 27.0o and Hausner’s ratio of 1.21 for Batch II that was selected for further studies) and no new peaks were formed from the Fourier Transform Infrared (FTIR) study conducted on the co – processed excipient. The result obtained revealed that, co – processing Maize Starch B.P. with α - lactose monohydrate will produce an excipient with desirable physicochemical properties suitable for pharmaceutical tablet formulations.